RETRACTED: The Influence Of Product Differentiation, Price Perception, And Brand Image On Wall's Ice Cream Purchasing Decisions At Lotte Mart South Jakarta City In 2020 - Sri Farah Dewi; elwisam elwisam; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the influence of Product Differentiation, Price Perception, and Brand Image on Wall's Ice Cream Purchasing Decisions at Lotte Mart South Jakarta City in 2020. This research data used primary data in the form of questionnaires to 100 consumers of Wall's ice cream at Lotte Mart South Jakarta City. Data analysis techniques using multiple linear regression analysis and using the SPSS program. The results showed an influence between Product Differentiation, on Purchasing Decisions by 0.205 and had an influence of 25.0%. Similarly, the Price Perception variable on Purchasing Decisions is 0.241 and has an influence of 24.1%. Then for the Brand Image variable on Purchase Decisions 0.266 and has an influence of 26.6%. Partially or simutan has a strong influence among the three variables, the most significant of which is the Brand Image variable of 0.266. The results of this study hope that Wall's Ice cream can stabilize the Brand Image that occurs at Lotte Mart in South Jakarta to support Purchasing Decisions.